Władza wykonawcza w Portoryko i w Polsce — porównanie oraz analiza wybranych uregulowań konstytucyjnych - Gutierrez, Patryk (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
In the paper entitled Executive Power in Puerto Rico and in Poland — the comparison and analysis of some constitutional issues, Idecided to compare two different constitutional regulations of executive power in Latin America and Europe Puerto Rico and Poland. At first glance, the both countries are republic with the same division of power between: executive, legislation and judicial. But on the other hand, the main differences have been established in the provisions of the Constitution. So, for this reason I’m trying to look for the answer for next questions: who performs the executive authority and whether this power is shared or not and how long it lasts during the term of office for example. Therefore, in my paper Ishowed the differences and similarities on this range: between Puerto Rican Governor with the Council of Secretaries and Polish President with the Council of Ministers.
Keywords: Constitution of Poland; Constitution of Puerto Rico; Executive Branch; President of Poland; Governor of Puerto Rico